2020
DOI: 10.2478/boku-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Energieeinsatz und Energieeffizienz von Winterweizen bei unterschiedlicher mineralischer Stickstoffdüngung im Marchfeld

Abstract: ZusammenfassungDie Korn- und Stroherträge, der Energie-Input (Kraftstoff, Mineraldünger, Pflanzenschutzmittel, Maschinen) und die Kennzahlen zur Energieeffizienz (Energie-Output, Netto-Energie-Output, Energieintensität, Energienutzungseffizienz) in Abhängigkeit der mineralischen Stickstoffdüngermenge (0 kg, 60 kg, 120 kg und 180 kg N ha−1) und der Düngerstrategie (unterschiedliche Mineraldüngerformen und Gabenteilungen) wurden auf zwei Standorten im Marchfeld (Engelhartstetten und Groß-Enzersdorf) auf Basis vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…The low differences in GY in our study support this observation. Especially, as every work operation is costing time and fuel and is affecting the energy efficiency of the production system [7,8,51].…”
Section: Nitrogen Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The low differences in GY in our study support this observation. Especially, as every work operation is costing time and fuel and is affecting the energy efficiency of the production system [7,8,51].…”
Section: Nitrogen Efficiencymentioning
confidence: 99%
“…But, fertilizer production energy is also the highest portion of the energy input in arable farming, even ahead of soil tillage [7]. The amount of fertilizer and the fertilizing strategy are influencing the energy efficiency, as shown for maize [8] and wheat [7]. An efficient N use is therefore a key indicator in sustainable plant production.…”
Section: Introductionmentioning
confidence: 99%
“…The fertilization strategy influences the amount of used fossil energy. In organic farming systems, where no mineral NPK is used, the total energy input is up to 65% lower than in NPK systems [11,12], as mineral fertilization consumes a lot of energy [10,[13][14][15], especially as process energy for the fertilizer production. Therefore, low-input systems are mainly based on FYM [16] as low-input agricultural systems have a greater energy use efficiency and lower greenhouse gas emissions compared to high-input systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…
Soil tillage is one of the highest energy and labor consumer in arable farming (Tabatabaeefar et al 2009, Szalay et al 2015. In conventional tillage systems with ploughing, more than 50% of total fuel consumption is usually used for soil preparation and seeding alone (Moitzi et al 2015). The establishment of winter wheat with no-tillage on a silty loam Chernozem could reduce both fuel consumption and work time by more than 85% compared to conventional tillage (Moitzi et al 2013).
…”
mentioning
confidence: 99%
“…Energy use efficiency rises with crop yield and can be improved by the nutrient management, i.e. the amount and kind of fertiliser (Moitzi et al 2020a). Deike et al (2008 found that crop yield and energy efficiency are much more affected by crop rotation than by tillage.…”
mentioning
confidence: 99%